Pengaruh Pendekatan Pendidikan Matematika Realistik Indonesia Terhadap Hasil Belajar Pecahan Senilai Siswa di Kelas IV SDN 16 Tarok Dipo - Sari, Rahmadian Fonika; Amini, Risda; Ahmad, Syafri (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
AbstractThis study aims to determine the effect of the Indonesian realistic education approach to the learning outcomes of fractions worth of students in class IV SDN 16 Tarok Dipo. The form of this research design is quasi experimental research of type non equivalent control group design. The sample in this study is class IVA and class IVB. The results of the calculation of the research data used is the t-test obtained by t count 3,08 > t table 1.67 at the level of α 0.05. Thus it can be concluded that there is a significant influence between the PMRI approach to the learning outcomes of fractions worth of students in class IV SDN 16 Tarok Dipo.  Keywords: PMRI approach, student learning outcomes, fractions worth